Liver Fibrosis Progression and Mortality in Hepatitis B– and C–Coinfected Persons Treated With Directly Acting Antiviral Agents: Results From ERCHIVES. (16th December 2019) - Butt, Adeel A; Yan, Peng; Aslam, Samia; Abou-Samra, Abdul-Badi; Sherman, Kenneth E; Shaikh, Obaid S
Abstract: For persons with baseline Fibrosis-4 1.46–3.25, cirrhosis incidence/1000 patient-years was 49.3 among hepatitis B virus (HBV)/hepatitis C virus (HCV) coinfected and 18.2 among HCV monoinfected ( P = .03). Cirrhosis risk was numerically higher but statistically nonsignificant among HBV/HCV coinfected (hazards ratio [HR] 1.51; 95% confidence intervals [CI], .37–6.05) but lower among those who attained sustained virologic response (HR, .52; 95% CI, .42–.63).